Synthesis of Tricarbonylchromium Complex of 1,2;5,6;9,10-Tribenzododeca-1,5,9-triene - Moshtaghi Zenouz, A. (Asian Journal of Chemistry, 2016)
The mono(tricarbonylchromium) complex of [2.2.2]orthocyclophane have been synthesized. The structure of this complex has been determined by 1H and 13C NMR spectroscopy.